Mapping the Dynamics of Subregional Order: Challenges and Prospects in the Maghreb Region after 2011 Arab Spring - Rafa, Asmaa; Amour, Philipp O. (Journal of Al-Tamaddun, 2023)
This article examines the security challenges facing the Maghreb region as a subregional system of the Middle East since the Arab Spring. The analysis concentrates on the period after the fall of the Libyan regime, which resulted in the decline of security in Libya, internal conflicts in Mali, and rising security instability in the Sahel region due to the return of Tuareg fighters to their Malian homeland. The article explores the political and economic dynamics in the Maghreb through an analysis of power distribution utilizing the regional security complex theory (RSCT). This examination highlights how these dynamics influence rivalry or cooperation, and the repercussions of missing systems that prompt the restructuring of the subregional order. The relevant information was systematically collected and analyzed via a data collection method which facilitated a thorough investigation of the intricate dynamics of the area, resulting in a better comprehension of the elements that mold its geopolitical environment.